Etude de quelques paramètres Biométriques et Nutritionnels chez un poisson, cas de l’espèce Sardinella aurita (Valenciennes,1847). - MEHIDI, Aymen (My University, 2024)
The allache Sardinella aurita (Valenciennes.1847) is a pelagic species of economic importance, omnipresent on the Algerian coast and abundant on almost all the fishing areas of the coast of Mostaganem, nevertheless there is almost a rarity at the level of stalls with a prohibitive price especially during the winter season.The objective of this research study is to implement on the one hand the biometric and reproduction parameters, and on the other hand to enhance the nutritional quality of the fish species Sardinella aurita. The research study focused on 120 individuals divided between 56 males and 64 females of this species during the four months, February, March, and April, and May 2024. We weighed the whole fish, and after dissection, we measured the weight of the liver and gonads, then took measurements of total and fork lengths, evaluated the gonado-somatic ratios (RGS) and hepatosomatic (RHS). For the estimation of the nutritional value was considered mainly by the calculation by mathematical formulas, of the percentage of dry matter, of the water content, the extraction of lipids from the skin and the flesh of the fish Sardinella aurita, and taking the pH following preparation of a solution containing distilled water and a fragment of the flesh. The evaluation of the sex ratio showed that the percentage of femininity is higher than that of males except during the month of March when the latter slightly exceeds that of females. During the four months from February to May we noticed that in males, the evolution of RGS is greater than RHS. At the same time in females the evolution of the RGS determines a high rate compared to the RHS. The relationship total size (Lt)-fork size (Lf) as a function of sex, presents the lowering allometry, and consequently the total length (Lt) increases relatively less rapidly than the fork length (Lf) and this for two sexes. The total length and weight relationship presents the increasing allometry, the mass increases proportionally faster than the length for both sexes.The percentage of dry matter MS (%) was estimated at 18%, and the water content at 82%. The percentage of lipids in the flesh of the fish was estimated at 07% and in the skin of the fish estimated at 86%. We therefore found that the lipid content in the skin is significantly higher than that found in the flesh. The measurement of the Ph of the sardine flesh by the pH meter was around 6.82 and that at its normal level. At the end of these results, we noted a slight female predominance, and that weight increases faster than height. The results of the parameters characterizing the nutritional value of Sardinella aurita agree with those found by other authors.
Keywords: Sardinella aurita; RGS; HRH; Sex ratio; Total length; Fork length; Weight; Allometry; Nutritional value